Khaled Abou El Fadl’s Hermeneutics as an Ethics of Living Islam: Religious Authority, Interpretive Authoritarianism, and Gender Justice - Yanuar Rizki Fauziah; Ali Murfi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This article analyzes Khaled Abou El Fadl’s hermeneutics as an ethical-philosophical framework for understanding religious authority, critiquing interpretive authoritarianism, and formulating an ethics of Islamic interpretation within the discourse of Living Islam. In this article, Living Islam is understood as an analytical framework that positions Islam as a living tradition shaped through the relationships among the text, authority, social practices, and Muslim experiences. This article addresses the limitations of previous studies, which have predominantly situated Abou El Fadl’s thought within the frameworks of Islamic law, fiqh reform, and critiques of authoritarian fatwas, but have not explicitly examined it as an ethics of Living Islam. This study employs a qualitative library-based research design using a critical-hermeneutic approach. The primary data sources include Abou El Fadl’s major works, while the secondary sources comprise literature on Islamic hermeneutics, Islamic legal authority, gender justice, qawwamun, qiwamah, lived religion, and lived Islam. Purposively selected sources were analyzed through document analysis, qualitative content analysis, and critical-hermeneutic interpretation. The findings demonstrate that interpretive authoritarianism emerges when interpreters foreclose the autonomy of the text and transform human interpretation into a final claim regarding God’s will. Abou El Fadl’s hermeneutics situates religious meaning within an ethical relationship among the author, the text, and the reader, while constraining interpretation through five moral prerequisites: honesty, diligence, comprehensiveness, reasonableness, and self-restraint. The interpretation of qawwamun underscores the importance of a contextual and justice-oriented approach to gender interpretation. The contribution of this article lies in its synthesis of a model of the ethics of Living Islam that connects the critique of authoritarianism, hermeneutic relationships, the moral prerequisites of interpreters, and the social consequences of interpretation for gender justice and contemporary Muslim realities.